2018
DOI: 10.21037/qims.2018.05.03
|View full text |Cite
|
Sign up to set email alerts
|

Aortic remodelling after thoracic endovascular aortic repair for acute and subacute type B aortic dissection

Abstract: TEVAR offers satisfactory results for the treatment of type B AD. Acute AD may be associated with better aortic remodelling compared to subacute AD after TEVAR.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 39 publications
0
7
0
Order By: Relevance
“…The maximum diameters of the aorta decreased obviously in the acute group, but they did not change significantly in the subacute group. These results indicated that acute AD may be associated with better aortic remodeling than subacute AD after TEVAR[55].…”
mentioning
confidence: 78%
“…The maximum diameters of the aorta decreased obviously in the acute group, but they did not change significantly in the subacute group. These results indicated that acute AD may be associated with better aortic remodeling than subacute AD after TEVAR[55].…”
mentioning
confidence: 78%
“…12 Another small case control study comparing a group of 22 patients with TBAD who were treated in the acute phase (<2 weeks) with a second group of 16 patients treated by TEVAR in the subacute phase (2 weekse3 months) has been reported. 13 Complication rates were similar, but aortic remodelling following TEVAR was more pronounced in the acute phase than in the subacute phase cohort. Thus, these results, coupled with those of the ADSORB trial, 9 along with other centres, 9,12,13 favour TEVAR during the acute dissection phase as a safe and efficacious treatment strategy.…”
mentioning
confidence: 90%
“…13 Complication rates were similar, but aortic remodelling following TEVAR was more pronounced in the acute phase than in the subacute phase cohort. Thus, these results, coupled with those of the ADSORB trial, 9 along with other centres, 9,12,13 favour TEVAR during the acute dissection phase as a safe and efficacious treatment strategy. So, where do we stand in terms of timing for TEVAR in patients with uncomplicated TBAD at this time?…”
mentioning
confidence: 90%
“…Probably it can prevent the late degenerations of the aneurysm or rupture of the dissected aortic segment as it was detected earlier in 20 to 50% of patients who applied OMT [3,4]. There were numerous clinical trials reported the remodeling process of the aorta after TEVAR treatment [5][6][7].…”
Section: Introductionmentioning
confidence: 99%